Prostaglandins participate in the late phase of the vascular response to acetylcholine iontophoresis in humans - Durand, S (Blackwell Science Inc, 2004)
The participation of prostaglandins (PGs) in the cutaneous vasodilatation to acetylcholine (ACh) applied via iontophoresis is under debate. Using laser Doppler flowmetry, we studied the long lasting effect (20 min) of iontophoretic application (30 s; 0.1 mA) of ACh on the human forearm. Experiments were repeated (1) using deionized water instead of ACh to test the effect of current application, (2) after scopolamine treatment to inhibit muscarinic cholinergic receptors, and (3) 2 h, 3 days and 10 days following inhibition of PG synthesis with aspirin or a placebo control. Cutaneous vascular conductance (CVC) was calculated at rest (CVC(rest)), at peak vasodilatation in the first 5 min following ACh iontophoresis (CVC(peak)), and 20 min after iontophoresis (CVC(20)). The minimal CVC (CVC(min)) following iontophoresis was also determined. Cutaneous response to ACh displayed a biphasic pattern with an early and transient peak (CVC(peak): 62 ± 8% of the maximal CVC induced by local heating (MVC)) followed by a long lasting slower vasodilatation (CVC(min): 44 ± 6; CVC(20): 56 ± 5%MVC). The current itself had no major effect. Scopolamine almost abolished both phases. The long lasting phase was aspirin sensitive but not the transient phase. At hour 2 post-aspirin, CVC(peak) was 61 ± 10, CVC(min) 26 ± 6 and CVC(20) 29 ± 6%MVC. At day 3, CVC(peak) was 53 ± 9, CVC(min) 22 ± 3 and CVC(20) 25 ± 4%MVC. At day 10, CVC(peak) was 67 ± 10, CVC(min) 47 ± 7 and CVC(20) 50 ± 8%MVC. Placebo had no effect. We conclude that PGs participate in the vasodilator response following ACh iontophoresis. Previous non-steroidal anti-inflammatory drug treatments must be taken into account when studying the effect of ACh iontophoresis.